External cold and vibration with BUZZY versus topical anesthetic gel for pain and anxiety associated with infiltrative anesthesia in pediatric dentistry: a double-blinded, split-mouth, randomized, controlled trial - Reyhaneh Faghihian; Mohammad Moin Tofighi; Sanaz Ziaei; Sayed Lotfollah Afzali (European Oral Research)
Purpose: A way to reduce the pain of injection is applying of external cold or vibrations with BUZZY, along with spinal cord gate control systems. We aimed to evaluate the effectiveness of this method in reducing children’s pain and anxiety during infiltrative anesthesia. Subjects and Methods: This was a double-blinded, randomized, split-mouth, controlled, trial. Thirty 6 to 12-year-old children with decayed first permanent molar tooth on both sides of their maxilla were enrolled. Each side of the children's mouths was randomly allocated to either BUZZY or topical anesthetic gel prior to infiltrative anesthesia. Pain and anxiety during infiltrative anesthesia were measured with the Baker-Wong (BWS), FLACC (Face, Leg, Activity, Cry, Consolability), and heart rate (HR) scales. Results: A generalized estimating equation (GEE) adjusted for age and baseline HR, indicated, significantly-lower intra-procedural HRs associated with BUZZY (aOR [95%CI]: 0.02 [0.00, 0.91], p=0.04). GEEs adjusted for age revealed the BWS (aOR [95%CI]: 0.59 [0.30, 1.14], p=0.12) and FLACC (aOR [95%CI]: 0.82 [0.62, 1.09], p=0.17) scores to be comparable between the study arms. Conclusion: Our study failed to demonstrate the superiority of BUZZY over anesthetic gels regarding WBS and FLACC measures of pain and anxiety, but demonstrated a decrease in HR associated with BUZZY.